Study of serum markers of bone mineral metabolism in patients with type 2 diabetes mellitus - V. Manolasya; Madhavi Gottam Bindhu; D. T. Katyarmal; Alok Sachan; M. M. Suchitra (Journal of Clinical and Scientific Research)
Background: Limited published data are available regarding markers of bone mineral metabolism among patients with type 2 diabetes mellitus (T2DM). Methods: In this cross-sectional study conducted in 100 subjects during the period March 2021 to July 2022 we studied the markers of bone mineral metabolism, namely, serum magnesium, calcium, inorganic phosphate and alkaline phosphatase in patients with T2DM (n = 50) and healthy controls (n = 50). Results: Both cases and controls were comparable in terms of age (P = 0.136) and gender (P = 0.68). Serum magnesium (mg/dL) (1.8 ± 0.3 Vs 2.1 ± 0.2; P < 0.001), and calcium (mg/dL) (8.4 ± 0.9 Vs 8.9 ± 0.7; P < 0.001) were significantly lower in cases compared with controls. Serum alkaline phosphatase (ALP) (IU/L) [105 (67.2-136.5) Vs 74 (54.8-108.5) was higher in cases compared to controls. Serum inorganic phosphate level (P = 0.093) and corrected calcium (P = 0.074) were within the normal range among cases and controls. Forty two out of 50 cases had poorly controlled T2DM [glycosylated haemoglobin (HbA1c) >7.0%]. Cases with poor glycaemic control had significantly lower serum magnesium levels compared with controlled diabetes (mg/dL) (1.7 ± 0.3 Vs 2.1 ± 0.2; P < 0.001). Serum magnesium levels were significantly lower in cases with macrovascular or microvascular complications compared with those without complications (1.760 ± 0.3 Vs 2 ± 0.2; P = 0.04). Conclusions: Cases had significantly lower serum magnesium, an important factor regulating parathormone secretion and action, compared to controls. Cases had significantly higher serum ALP level compared to controls, indicating the increased bone turnover, among patients with T2DM when compared to healthy individuals.